Somalia Economic Update, August 2019 : Building Education to Boost Human Capital - World Bank (World Bank, Washington, DC, 2019)
The economy is recovering slowly from drought, but Somalia continues to face significant challenges.The Somali economy rebounded in 2018 from the 2016/17 drought.Public finances continued to strengthen in 2018.Credit to the private sector grew rapidly in 2018, and Somalia’s financial sector supervisory capacity continued to strengthen.The current account deficit declined slightly.The medium-term outlook is for a moderate increase in GDP growth.This outlook is subject to significant risks and depends on continued policy reforms. Key risks to medium-term growth prospects include security concerns, weather and climatic shocks, and political uncertainty. The authorities have been developing a track record of reform in areas of revenue mobilization, expenditure control, and financial sector regulation. Important challenges remain, however.A slowdown in the reform momentum would not only undermine medium-term economic growth, but also could delay the normalization of Somalia’s relations with international financial institutions and access to critical external resources needed for development.Finally, Somalia needs to accelerate economic growth and reorient government spending towards public investment, particularly investment to boost human capital.